2021
DOI: 10.1021/acsphotonics.1c00045
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Single-Molecule Fluorescence Spectroscopy with Simple and Robust Hybrid Nanoapertures

Abstract: Plasmonic nanoapertures have found exciting applications in optical sensing, spectroscopy, imaging, and nanomanipulation. The subdiffraction optical field localization, reduced detection volume (∼attoliters), and background-free operation make them particularly attractive for single-particle and single-molecule studies. However, in contrast to the high field enhancements by traditional "nanoantenna"-based structures, small field enhancement in conventional nanoapertures results in weak light−matter interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…She is working alongside Dr Yuebing Zheng and his research group, and her research interests lie in optical manipulation and the manipulation of micro/nanoparticles. nanofabrication, [53][54][55][56][57][58] chemical and biological sensing, [59][60][61] and cargo delivery. 62,63 Based on this, optothermal rotation has been further developed recently for precise and versatile rotations of colloidal particles and living cells with striking advantages such as low operation power, high applicability, and long working distance.…”
Section: Carolina Poncementioning
confidence: 99%
See 1 more Smart Citation
“…She is working alongside Dr Yuebing Zheng and his research group, and her research interests lie in optical manipulation and the manipulation of micro/nanoparticles. nanofabrication, [53][54][55][56][57][58] chemical and biological sensing, [59][60][61] and cargo delivery. 62,63 Based on this, optothermal rotation has been further developed recently for precise and versatile rotations of colloidal particles and living cells with striking advantages such as low operation power, high applicability, and long working distance.…”
Section: Carolina Poncementioning
confidence: 99%
“…Over the past two decades, researchers have established multiple theories to describe the translational migration of colloids and living objects under temperature gradient fields. [31][32][33][34][35][36] Consequently, different optothermal manipulation techniques have been developed, [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] leading to applications in nanofabrication, [53][54][55][56][57][58] chemical and biological sensing, [59][60][61] and cargo delivery. 62,63 Based on this, optothermal rotation has been further developed recently for precise and versatile rotations of colloidal particles and living cells with striking advantages such as low operation power, high applicability, and long working distance.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic tweezers 93 offer the right combination of site specificity and controlled heat generation, which enables plasmon-enhanced optical or optothermal trapping along with optothermal delivery of target particles. 94 Using plasmonic nanostructures as substrates, target particles are attracted from long-range distances and trapped locally and stably at the nanostructures due to the enhanced electromagnetic and temperature hot spots. 97,99 The highly localized electric field enhancements lead to a high trapping stiffness of different entities such as DNA, proteins, nanoparticles, and quantum dots.…”
Section: Analytical Modeling Challenges Of Optothermal Manipulationmentioning
confidence: 99%
“…Although optothermal tweezers on solid substrates arose as a promising solution, other techniques are essential to overcome the problem in liquid media. Plasmonic tweezers offer the right combination of site specificity and controlled heat generation, which enables plasmon-enhanced optical or optothermal trapping along with optothermal delivery of target particles. Using plasmonic nanostructures as substrates, target particles are attracted from long-range distances and trapped locally and stably at the nanostructures due to the enhanced electromagnetic and temperature hot spots. , The highly localized electric field enhancements lead to a high trapping stiffness of different entities such as DNA, proteins, nanoparticles, and quantum dots. Initial studies did not include the effects of thermophoretic force on particle trapping, mainly due to negligible thermophoretic force at the singularity.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Regarding the fluorescence brightness, several studies have reported fluorescence enhancement of the photon count rate for diffusing molecules. , On the contrary, for immobilized single molecules, the results are less documented and appear sometimes to be contradictory. Aluminum ZMWs were shown to enhance the fluorescence brightness of green dyes Atto 550 and Atto 565 by 2.2- and 2.5-fold, respectively. , However, for the red dye Atto 647N, either 2.5-fold enhancement, no enhancement, or 10-fold lower brightness , was reported.…”
Section: Introductionmentioning
confidence: 99%